A simulation-based curriculum to introduce key teamwork principles to entering medical students. Issue 1 (December 2016) - Banerjee, Arna; Slagle, Jason; Mercaldo, Nathaniel; Booker, Ray; Miller, Anne; France, Daniel; Rawn, Lisa; Weinger, Matthew
Abstract Background Failures of teamwork and interpersonal communication have been cited as a major patient safety issue. Although healthcare is increasingly being provided in interdisciplinary teams, medical school curricula have traditionally not explicitly included the specific knowledge, skills, attitudes, and behaviors required to function effectively as part of such teams. Methods As part of a new "Foundations" core course for beginning medical students that provided a two-week introduction to the most important themes in modern healthcare, a multidisciplinary team, in collaboration with the Center for Experiential Learning and Assessment, was asked to create an experiential introduction to teamwork and interpersonal communication. We designed and implemented a novel, all-day course to teach second-week medical students basic teamwork and interpersonal principles and skills using immersive simulation methods. Students' anonymous comprehensive course evaluations were collected at the end of the day. Through four years of iterative refinement based on students' course evaluations, faculty reflection, and debriefing, the course changed and matured. Results Four hundred twenty evaluations were collected. Course evaluations were positive with almost all questions having means and medians greater than 5 out of 7 across all 4 years. Sequential year comparisons were of greatest interest for examining the effects of year-to-year curricular improvements. Differences were not detected among any of the course evaluation questions between 2007 and 2008 except that more students in 2008 felt that the course further developed their "Decision Making Abilities" (OR 1.69, 95% CI 1.07–2.67). With extensive changes to the syllabus and debriefer selection/assignment, concomitant improvements were observed in these aspects between 2008 and 2009 (OR = 2.11, 95% CI: 1.28–3.50). Substantive improvements in specific exercises also yielded significant improvements in the evaluations of those exercises. Conclusions This curriculum could be valuable to other medical schools seeking to inculcate teamwork foundations in their medical school's preclinical curricula. Moreover, this curriculum can be used to facilitate teamwork principles important to inter-disciplinary, as well as uni-disciplinary, collaboration.